Development of microencapsulated phase change material for solar thermal energy storage - Su, Weiguang; Darkwa, Jo; Kokogiannakis, Georgios (Elsevier, 2017)
In this paper a novel microencapsulated phase change material (MF-3) has been developed and tested for solar assisted hot water storage systems. Even though the morphology of the sample was affected by the type of emulsifier used for fabrication it recorded the highest energy storage capacity of 126 kJ/kg with encapsulation efficiency of 97.4% as compared with other developed samples. For the purpose of assessing its thermal effectiveness it was theoretically evaluated in a compacted fixed bed TES unit and found to be capable of achieving a higher energy storage density as well as relatively smaller physical storage size than water based system. Despite the overall effective thermal conductivity being slightly less than water, its value was still about twice as high as most current PCM storage units. Experimental evaluation is therefore strongly encouraged.